Pengaruh Variasi Disintegran Avicel PH-102 dan Primogel terhadap Karakteristik Co-Processed Excipient - Hilya Nur Imtihani; Sinda Alfreeda; Jade Rhea Almira Arif (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2023)
The direct compression method is one of the most popular tablet manufacturing methods because of its efficiency. However, direct compression requires excipients with good flow and compressibility properties. The requisite for materials with these properties can be overcome by using co-processed excipients. The co-processed excipient combines two or more types of excipients that aim to improve flow properties and compressibility. This study aims to determine the effect of differences in Avicel PH-102 (F1=10%; F2=15%) and Primogel (F3=4%; F4=8%) variations as disintegrants on the characteristics of co-processed excipients. The excipients include lactose as filler, Avicel PH-102 or primogel as a disintegrant, and PVP K-30 as a binder. The method of preparation co-processed excipient used was wet granulation. The results showed that the granule flow rate was F1=14.62 g/second, F2=11.30 g/second, F3=19.31 g/second, and F4=11.57 g/second. The angle of repose of the granules was F1=11.30˚, F2=19.24˚, F3=13.97˚, and F4=20.78˚. Compressibility and Hausner granule ratio F1=12% and 1.13; F2=17.81% and 1.21; F3= 7.12% and 1.07; and F4 = 16.51% and 1.19. Percentage of moisture content of granules F1=4%, F2=3.67%, F3=3%, and F4=3.67%. Percentage of fines granule F1 = 18.42%, F2 = 9.14%, F3 = 4.06%, and F4 = 2.65%. The evaluation results were statistically tested using the SPSS one-way ANOVA or Kruskall Wallis. All formulas in this study were able to produce co-processed excipients that met the requirements, and there were significant differences except for the water content parameter.